Adolescent school phobia: its causes, treatments, and implications - Ostrem, Christine (My University, 1985)
This study examined the causes, characteristics, and treatments of adolescent school phobia. School phobia is the most commonly seen phobia in school age children and adolescents. Students who experience school phobia exhibit an extreme fear of school or some aspect of the school situation. The student exhibits somatic symptoms while preparing to go to school or while in the classroom. These somatic complaints hinder students' abilities to learn and their relationships with peers. While younger children suffer from a form of separation anxiety, the school phobia exhibited by adolescents is characteristic of a deep seated neurosis which may be linked to a familial pattern of neuroses. Treatment is advised for the entire family. The goal of all treatments is to get the child back to school as soon as possible. Treatment perspectives examined were: psychoanalytical, psychodynamic, behavioral, and learning theory approaches. This study presented suggestions for use by parents, educators, and school psychologists/counselors who deal with school phobic adolescents in the home, classroom, or counseling environment.
Keywords: School phobia